Effects of Altitude on the Digestion Performance, Serum Antioxidative Characteristics, Rumen Fermentation Parameters, and Rumen Bacteria of Sanhe Heifers - Zhang, Xinyu; Huang, Shuai; Li, Shengli; Wang, Wei (Frontiers in Microbiology, 2022)
The production efficiency of dairy cows is affected by altitude, with lower efficiency reported at higher altitudes. However, only a few studies have investigated the digestion metabolism, rumen fermentation performance, and rumen microbiota of Sanhe heifers at different altitudes. Therefore, in this study, we explored the effects of altitude on these aspects of Sanhe heifers. We evaluated the effects of altitude on the apparent digestibility of nutrients, serum antioxidative characteristics, rumen fermentation parameters, and rumen microbiota in Sanhe heifers. Twenty Sanhe heifers from two regions of China were examined: 10 from Hulunbuir City, Inner Mongolia Autonomous Region (119°57ʹE, 47°17ʹN; approximately 700 m of altitude, named LA), and 10 from Lhasa City, Tibet Autonomous Region (91°06ʹE, 29°36ʹN; approximately 3,750 m of altitude, named HA). The dry matter intake (DMI), average daily gain (ADG), and DMI/ADG ratio were higher (P < 0.05) in LA than in HA heifers, whereas the apparent total tract digestibility of dry matter, ether extract, and crude proteins were higher (P < 0.05) in the HA group. Compared with LA heifers, the HA heifers decreased (P < 0.05) the concentrations of superoxide dismutase and glutathione peroxidase in the serum of Sanhe heifers and increased the serum level of hydrogen peroxide (P < 0.05). Altitude did not significantly affect the volatile fatty acid concentration in the rumen, but HA presented a lower acetate-to-propionate ratio. The 16S rRNA gene sequencing data showed that altitude significantly affected the rumen microbial composition. At the phylum level, the HA heifers presented a lower relative abundance of Actinobacteria (P < 0.05) and higher relative abundance of Spirochaetae (P < 0.05) than the LA heifers. The correlation analysis revealed that the operational taxonomic units belonging to the genus Prevotella_1 were correlated (P < 0.05) with altitude and DMI. The results indicate that altitude can influence the apparent digestibility of nutrients, serum antioxidant capacity, rumen fermentation, and rumen microbiota composition of Sanhe heifers. The study provides insights into the adaptation mechanism of Sanhe heifers to high-altitude areas.